Nanotechnology what will it mean?. - Merkle, R.C (IEEE spectrum)
Nanotechnology will make us healthy and wealthy though not necessarily wise. In a few decades, this emerging manufacturing technology will let us inexpensively arrange atoms and molecules in most of the ways permitted by physical laws. It will let us make supercomputers that fit on the head of a pin and fleets of medical nanorobots smaller than a human cell able to eliminate cancer, infections, clogged arteries, and even old age. People will look back on this era with the same feelings we have toward medieval times-when technology was primitive and almost everyone lived in poverty and died young. Besides computers billions of times more powerful than today's, and new medical capabilities that will heal and cure in cases that are now viewed as utterly hopeless, this new and very precise way of fabricating products will also eliminate the pollution from current manufacturing methods. Molecular manufacturing will make exactly what it is supposed to make, no more and no less, and therefore won't make pollutants. However it should be remembered that as well as being used for great good, nanotechnology could also be used to do great harm. The implications of this are discussed